Current status and correlation of disease perception, self-transcendence and resilience in young and middle-aged patients with cerebral hemorrhage - CHONG Ke; SHI Yuan; NIU Yuan; LIU Liqin (Yixue xinzhi zazhi)
Objective Understanding the current status of disease perception, self-transcendence, and resilience levels in young and middle-aged patients with cerebral hemorrhage and their relationship to short-term prognosis.Methods General data of young and middle-aged cerebral hemorrhage patients admitted to the Department of Neurosurgery of the Second Affiliated Hospital of the Air Force Medical University from April 2020 to April 2023, were colected and the patients' disease perception, self- transcendence, and resilience levels were evaluated relevant questionnaires. Pearson correlation analysis was analyzed to explore the correlation among the three scores and multivariate Logistic regression analysis was performed to explore the risk factors for patients' short-term prognosis.Results A total of 142 young and middle-aged patients with cerebral hemorrhage were included, including 32 cases in the poor prognosis group and 110 cases in the good prognosis group. Positive perceptions of illness were positively correlated with self-transcendence (r=0.461) and resilience (r=0.449); negative perceptions of illness were negatively correlated with self-transcendence (r=-0.513) and resilience (r=-0.482); and self-transcendence was positively correlated with resilience (r=0.558). Multivariate Logistic regression analysis showed that irregular hematoma morphology [OR=2.065, 95%CI(1.750, 2.379)], high disease negative perception score [OR=2.230, 95%CI(1.902, 2.558)], low self-transcendence score [OR=2.423, 95%CI(1.954, 2.892)], low resilience score [OR=2.018, 95%CI(1.452, 2.584)], high level interleukin-6 [OR=2.044, 95%CI(1.701, 2.387)], high level ferritin [OR=2.081, 95%CI(1.635, 2.528)] were risk factors for short-term prognosis in young and middle-aged patients with cerebral hemorrhage (P